(untitled) (AYUSHDHARA, 2025)
Bronchial hyper responsiveness and variable air flow obstruction is the primary causes of episodes of breathlessness, coughing, wheezing, tightness in the chest, among other symptoms of bronchial asthma, a chronic inflammatory disease that may be treated or resolved on its own. When combined with traditional treatments, homeopathic treatment of bronchial asthma shows promise as a supplemental strategy. Although early data points to its possible advantages, more study is required to develop firm clinical recommendations and confirm the efficacy of homeopathic remedies in the management of asthma. An estimated 15–20 million people in India suffer from asthma. About 2% of people in India have it. It contributes to a lower quality of life by limiting physical activity (69%), making it harder to accomplish everyday tasks (85%), and decreasing productivity at work (73%), study (64%), and limits in leisure and lifestyle (78%). Since Homeopathy is founded on the laws of similar, it treats illnesses by using medications that, when administered to healthy people, cause symptoms that are similar. A person is treated holistically with homeopathy. There are medications available to treat acute asthma attacks, stop them from happening again, and address allergens that can cause an asthma attack.